F.S.F Co - Mohd Hasat @ Arshad, Mohd Shafiq; Hamdin, Mohd Farhan; Nahilin, Mohd Firhan (2017)
F.S.F Co is company that produced bracelet located in Kota Kinabalu , Sabah, 88400, Malaysia that allows the entire family to have their bracelet needs satisfied in one convenient location. F.S.F Co serves men, women, and children and accepts appointments as well as subscribe. F.S.F Co also sells accessery. F.S.F Co is able to serve the entire family in one quick, convenient visit. While there are many "quick shop" like F.S.F Co, F.S.F Co will excel due to its attention to detail regarding customer service. Through unheralded customer attention, F.S.F Co will slowly but surely gain market share as it services the entire family, creating long-term relationships. Lastly F.S.F Co location will allow it to attract a lot of walk in traffic. People across Malaysia have decided to use our services when they want to fulfil their accesories need, for example to have their bracelet or to make over their appearance through different bracelet style. F.S.F Co has foreseen this opportunity to provide the finest and highest quality of bracelet and styling to all people, despite their age or gender. This has shown that F.S.F Co has the calibre to be one of the most successful simple bracelet in Malaysia. We, F.S.F Co, saw the opportunity that this business has the potential of success provided that it is handled efficiently. The people have always needed to take care of their bracelet, as the bracelet reflects their personality, and to make them feel more confidence and comfortable. F.S.F Co sees this as a way to prosper in this market, by taking advantage of all these people"s need.